2020
DOI: 10.1155/2020/6694214
|View full text |Cite
|
Sign up to set email alerts
|

Bergenin Attenuates Hepatic Fibrosis by Regulating Autophagy Mediated by the PPAR-γ/TGF-β Pathway

Abstract: Liver fibrosis is a pathological process involving diffuse extracellular matrix (ECM) deposition in the liver. It is typical of many chronic liver diseases, including cirrhosis, and effective drugs are needed. In this study, we explored the protective effect of bergenin on liver fibrosis induced by carbon tetrachloride and bile duct ligation. A variety of molecular biological methods (qRT-PCR, western blotting, and immunohistochemistry) were employed to confirm the increased degree of hepatocyte injury and ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…49,50 Simultaneously, several studies showed that bergenin acted as an agonist of PPAR-γ when exerted its several biological activities. 32,[51][52][53] Particularly, Wang et al demonstrated that bergenin could ameliorate colitis in mice through banding PPAR-γ, then inhibiting the activation of NF-κB in macrophage. 53 In order to find out whether PPARγ-dependent pathway involved in the protective effect of bergenin in H 2 O 2 -induced HNPCs, we used western blot to measure PPAR-γ.…”
Section: Results Indicated That Treatment With Bergenin Significantly...mentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Simultaneously, several studies showed that bergenin acted as an agonist of PPAR-γ when exerted its several biological activities. 32,[51][52][53] Particularly, Wang et al demonstrated that bergenin could ameliorate colitis in mice through banding PPAR-γ, then inhibiting the activation of NF-κB in macrophage. 53 In order to find out whether PPARγ-dependent pathway involved in the protective effect of bergenin in H 2 O 2 -induced HNPCs, we used western blot to measure PPAR-γ.…”
Section: Results Indicated That Treatment With Bergenin Significantly...mentioning
confidence: 99%
“…PPAR‐γ has been reported to protect neurons from ROS‐induce oxidative damage 48 and its antioxidant capacity was associated with NF‐κB suppression 49,50 . Simultaneously, several studies showed that bergenin acted as an agonist of PPAR‐γ when exerted its several biological activities 32,51–53 . Particularly, Wang et al demonstrated that bergenin could ameliorate colitis in mice through banding PPAR‐γ, then inhibiting the activation of NF‐κB in macrophage 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation, Xia and his research team assessed the defensive effect of BER on hepatic fibrosis via bile duct ligation and carbon tetrachloride. In this study, BER was observed as a potential bioactive for the management of hepatic fibrosis [70].…”
Section: Hepatoprotectivementioning
confidence: 87%
“…PPARγ can regulate the TGF-β/Smads pathway and binds directly to Smad3 and inhibits TGF-β-induced CTGF and α-SMA expression in smooth muscle cells [ 82 ]. Several molecules that upregulate PPARγ can inhibit TGF-β production during fibrosis in different tissues [ 83 , 84 ]. PPARγ is involved in HSC transdifferentiation and fibroblast transformation, PPARγ2 is highly expressed in quiescent HSC, and PPARγ is downregulated during HSC activation [ 85 ].…”
Section: Role Of Ppars In Liver Diseasesmentioning
confidence: 99%